Perspective of collegiate athletes on team building sharing meals between coaches and athletes after training and games - Suelto, Franco Gabriel V. 1999-; Dizer, Ronualdo (Quezon City College of Human Kinetics, University of the Philippines Diliman, 2023)
The purpose of this study is to conduct a qualitative exploration on the perspective of collegiate athletes about team building, specifically on how sharing meals between teams and coaches can promote team cohesion and improve team chemistry. The literature on relationships inside and outside the court as well as team building and team chemistry highlights the unique lifestyles that promote team cohesion in a sporting context. A comprehensive, semi-structured interview with 12 participants from four different teams who take part in UAAP competitions was part of the qualitative procedure. The data was interpreted using descriptive analysis. Communication with teammates and coaches during meals was vital to a team's overall performance as it reflects team chemistry, especially during training and when coping with academic and athletic responsibilities. According to the findings, student-athletes value consistent communication with their teammates and coaches, and believe that they can achieve and foster team chemistry through sharing meals regularly. A notable finding from the study is that the exchanges that happen when the teams are sharing meals after games and training mostly involves an athlete’s personal life yet few discussions about the sport itself. This study demonstrates the significance of communication within the team while incorporating traditional styles of instilling positive social connection.
Vita
Thesis (Bachelor of Sport Science) -- University of the Philippines Diliman
Includes bibliographical references
Keywords: College athletes; Coach-athlete relationship